1977
DOI: 10.3109/14017437709167807
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Valve Replacement with the Björk-Shiley Prosthesis in Young Patients

Abstract: Between 1971 and 1974, 26 valve replacements with the Björk-Shiley tilting disc valve prosthesis were performed in 23 children between 4 and 16 years of age. Mitral valve replacement was carried out in 11 patients, aortic valve replacement in 9 and double replacement in the other 3 patients. Several of the patients presented associated lesions which were also corrected at the same intervention, One patient died during the postoperative period; the remaining 22 all showed significant clinical remission. No inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These authors commented that a number of early reports had shown that those children taking aspirin or no medications had both few embolic complications and no episodes of bleeding. Notably Rufilinchas and colleagues [42] observed no bleeding or thromboembolic complications in 22 children who underwent valve replacement of Bj6rk-Shiley valves without the use of warfarin. We at Great Ormond Street have not been as brave as this, first because thromboembolic episodes tend to be time related and are thus likely to occur during longer follow-up periods, and second because the evidence for antithrombotic effects of aspirin and of dipyridamole is not wholly convincing and has recently been challenged [43].…”
Section: Anticoagulationmentioning
confidence: 96%
“…These authors commented that a number of early reports had shown that those children taking aspirin or no medications had both few embolic complications and no episodes of bleeding. Notably Rufilinchas and colleagues [42] observed no bleeding or thromboembolic complications in 22 children who underwent valve replacement of Bj6rk-Shiley valves without the use of warfarin. We at Great Ormond Street have not been as brave as this, first because thromboembolic episodes tend to be time related and are thus likely to occur during longer follow-up periods, and second because the evidence for antithrombotic effects of aspirin and of dipyridamole is not wholly convincing and has recently been challenged [43].…”
Section: Anticoagulationmentioning
confidence: 96%